2017
DOI: 10.1039/c6sm02725c
|View full text |Cite
|
Sign up to set email alerts
|

Minimum free-energy paths for the self-organization of polymer brushes

Abstract: A methodology to calculate minimum free-energy paths based on the combination of a molecular theory and the improved string method is introduced and applied to study the self-organization of polymer brushes under poor solvent conditions. Polymer brushes in a poor solvent cannot undergo macroscopic phase separation due to the physical constraint imposed by the grafting points; therefore, they microphase separate forming aggregates. Under some conditions, the theory predicts that the homogeneous brush and the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…Metastable structures cannot be described by the theory reported in this work, but it may be possible to study transitions between them in the future using the recently reported molecular theory/string method formalism. 45 The theory predicts the occurrence of a micelle→fiber→lamella transition when the size of the tail or linker blocks is increased, which is in qualitative agreement with experimental results for peptide amphiphiles [14][15][16][17] and long diblock copolymers. 38 This prediction is also consistent with Israelachvili's packing theory, 30,31 as we showed by calculating the packing parameter of Israelachvili's theory using our theory.…”
Section: Discussionsupporting
confidence: 82%
“…Metastable structures cannot be described by the theory reported in this work, but it may be possible to study transitions between them in the future using the recently reported molecular theory/string method formalism. 45 The theory predicts the occurrence of a micelle→fiber→lamella transition when the size of the tail or linker blocks is increased, which is in qualitative agreement with experimental results for peptide amphiphiles [14][15][16][17] and long diblock copolymers. 38 This prediction is also consistent with Israelachvili's packing theory, 30,31 as we showed by calculating the packing parameter of Israelachvili's theory using our theory.…”
Section: Discussionsupporting
confidence: 82%
“…There is a free energy barrier expected between the two phases and the diblock copolymer nanogate could stay in a metastable state for a time scale that depends on the height of the energy barrier. For neutral homopolymer brushes grafted on flat surfaces, such a free energy barrier has been recently demonstrated by Gleria et al using a molecular theory combined with the improved string method . In this present study, we test the stabilities of the two phases at varying pHs and are able to estimate the boundaries of pH window for the coexistence as shown in Figure B.…”
Section: Resultsmentioning
confidence: 53%
“…For neutral homopolymer brushes grafted on flat surfaces, such a free energy barrier has been recently demonstrated by Gleria et al using a molecular theory combined with the improved string method. 67 In this present study, we test the stabilities of the two phases at varying pHs and are able to estimate the boundaries of pH window for the coexistence as shown in Figure 3B. The dashed curve in Figure 3B shows the free energy difference between the two phases ΔF = F center − F wall .…”
Section: Polymer Sequence Design and Gate Architecturementioning
confidence: 95%
“…In previous studies of polymer brushes in poor solvent conditions, we have observed the possibility of having bistable systems in equilibrium, where the molecular theory predicted the existence of more than one local free-energy minima with very different morphologies. , In order to test whether bistability is present in the current system, we solved the molecular theory for increasing values of the applied potential until we obtained the conformational transition, and then we decreased the electric field back to the equilibrium condition ( E = 0). The results of this calculation (Figure ) show that for some values of E , two different structures can be obtained, which indicate that this system is bistable.…”
Section: Results and Discussionmentioning
confidence: 99%